High-dose Humanin analogue applied during ischemia exerts cardioprotection against ischemia/reperfusion injury by reducing mitochondrial dysfunction - Savitree Thummasorn (2018)
© 2017 John Wiley & Sons Ltd Aim: Although the gold standard treatment for acute myocardial infarction is reperfusion therapy, reperfusion itself can cause myocardial damage via induction of cardiac mitochondrial dysfunction. This can lead to increased myocardial infarct size, arrhythmias, and left ventricular (LV) dysfunction. Recently, a newly discovered peptide, Humanin, has been shown to exert several beneficial effects including antioxidative and antiapoptosis effects. We recently reported that a Humanin analogue (HNG, 84 μg/kg) given prior to cardiac ischemia exerted cardioprotection against I/R injury, but failed to do so when it was given after ischemia was induced. However, in a clinical setting, patients can only be treated after the onset of ischemia. In this study, we investigated the potential benefit of various doses of HNG therapy (84, 168, 252 μg/kg) against myocardial I/R injury when applied during ischemia on cardiac arrhythmia, myocardial infarct size, cardiac mitochondrial function, and LV function. Methods: Myocardial I/R injury was induced in rats by 30-minute left anterior descending coronary artery occlusion, followed by 120-minute of reperfusion. HNG at the different doses were given intravenously at 15 minutes after ischemic onset and also at the onset of reperfusion. Results: HNG (252 μg/kg) applied during the ischemic period not only increased HN levels in the damaged myocardium, but also significantly decreased cardiac arrhythmia, myocardial infarct size, cardiac mitochondrial dysfunction, and left ventricular dysfunction. These benefits were mediated through the attenuation of cardiac mitochondrial dysfunction. Conclusions: High-dose HN applied during ischemia in rats could exert cardioprotection against I/R injury-induced mitochondrial dysfunction.